2023
DOI: 10.3389/fnut.2023.1079799
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of donkey-meat flavor profiles by GC–IMS and multivariate analysis

Abstract: The distinctive flavor compounds of donkey meat are unknown. Accordingly, in the present study, the volatile compounds (VOCs) in the meat from SanFen (SF) and WuTou (WT) donkeys were comprehensively analyzed by gas chromatography–ion mobility spectrometry (GC-IMS) combined with multivariate analysis. A total of 38 VOCs, of which 33.33% were ketones, 28.89% were alcohols, 20.00% were aldehydes, and 2.22% were heterocycles, were identified. Ketones and alcohols were significantly more abundant for SF than for WT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…2 ), including 2-pentanone (ROAV=78.21–100.00), hexanal (ROAV=17.35–39.35), nonanal (ROAV=16.95–55.09), octanal (ROAV=15.01–38.63), 3-methylbutanal (ROAV=9.48–25.84), heptanal (ROAV= 3.74–14.98), acetone (ROAV=2.58–10.22), 2-butanone (ROAV=2.82–4.10), ethyl acetate (ROAV=1.08–3.20), and 2-octanol (ROAV=0.59–2.02). This is consistent with our previous study, in which heptanal, 1-octen-3-ol, ethyl acetate, and hexanal with OAVs≥1 were determined to be the predominant flavor compounds in donkey meat ( Man et al, 2023b ). The characteristic flavors of meats and their products has been extensively analyzed in recent years ( Sohail et al, 2022 ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…2 ), including 2-pentanone (ROAV=78.21–100.00), hexanal (ROAV=17.35–39.35), nonanal (ROAV=16.95–55.09), octanal (ROAV=15.01–38.63), 3-methylbutanal (ROAV=9.48–25.84), heptanal (ROAV= 3.74–14.98), acetone (ROAV=2.58–10.22), 2-butanone (ROAV=2.82–4.10), ethyl acetate (ROAV=1.08–3.20), and 2-octanol (ROAV=0.59–2.02). This is consistent with our previous study, in which heptanal, 1-octen-3-ol, ethyl acetate, and hexanal with OAVs≥1 were determined to be the predominant flavor compounds in donkey meat ( Man et al, 2023b ). The characteristic flavors of meats and their products has been extensively analyzed in recent years ( Sohail et al, 2022 ).…”
Section: Resultssupporting
confidence: 93%
“…A FlavourSpec ® Flavour HS–GC–IMS instrument (Shandong Haineng Scientific Instrument, Shandong, China) was used to analyze the donkey meat samples. Analysis method for the VOCs in samples based on relevant references with few modifications ( Man et al, 2023b ). Briefly, a 1.5 g minced meat sample was placed into a 20 mL headspace vial and incubated at 60°C for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, 3-methylbutyl acetate, 3-methylbutanoic acid, 2-pentanone D, 2-heptanone D, 1-hexanol, phenylacetaldehyde, 2-butanone, and ethanol exhibited significant differences between the four breeds. These findings indicate that GC-IMS analysis can rapidly distinguish between chicken meat samples from the four breeds, consistent with previous studies on different pork and donkey meat varieties [ 22 , 25 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that the VOCs in meat are breed-dependent [ 22 , 32 ]. Our present study aligns with these findings and reveals that VOCs in chicken meat are also breed-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation